Studi Perencanaan Trotoar Di Dalam Lingkungan Kampus Universitas Sriwijaya Inderalaya - Novalino Pratama (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2014)
Planning sidewalks within the campus of the University of Sriwijaya in Inderalaya is idea in developing and providing space on the campus of pedestrian walkways, especially sidewalks is one of the typologies of pedestrian space. Occured Conflicts between pedestrians with vehicles as road users because pedestrian space is still minim in the campus environment so need for planning in providing a pedestrian space. In this study, the beginning of a planning study conducted observations pedestrian sidewalk that is within the campus environment, especially on the point that a lot of the number of pedestrians and frequent the presence of pedestrian activity, further research is assisted with example the planning of a university that had planned pedestrian space well such as the university of alabama as a reference in planning pedestrian path space. Based on the results of studies and surveys on the campus submitted that the pedestrian is in the campus as a mode of transport dominate the activity in the neighborhood Sriwijaya University, 6-10 minutes travel time, support facilities pedestrian is a seating of pedestrian that become the attention of user, the overall of the pedestrian within the campus of the University of Sriwijaya agreed with the plan provision and development of pedestrian walkways as space for pedestrian. Key Words: Planning sidewalks, Pedestrian, Development of pedestrian walkways